2014
DOI: 10.32508/stdj.v17i4.1536
|View full text |Cite
|
Sign up to set email alerts
|

Germination and seedling growth of Brassica juncea and Medicago sativa under exposure to microcystinscontaminated water from Dau Tieng reservoir

Abstract: Occurrence of toxic cyanobacteria and their toxins has been a root of many consequently serious problems to aquatic plants, animals, and human in the world. However, the toxicity of cyanobacterial toxins from Vietnam waters to the germination and growth of plants has not studied yet. In this study, we investigated the effects of microcystins (MC) (at the concentrations of 20 and 200 µg MC L-1) from field water and crude extract of cyanobacterial scum (mainly Microcystis spp.) from the Dau Tieng Reservoir, on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that crude extracts of the cyanobacteria with MC and without MC caused different effects on seed germination and initial development of the salad green seedlings, and lettuce being more sensitive to both extracts when compared to arugula [9]. In addition Dao et al (2014) [10] shown that the germination and seeding growth of some vegetables were damaged under exposure to microcystins contaminated water from the Dau Tieng reservoir. Agricultural plants showed differently response to cyanobacteria producing microcystins.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that crude extracts of the cyanobacteria with MC and without MC caused different effects on seed germination and initial development of the salad green seedlings, and lettuce being more sensitive to both extracts when compared to arugula [9]. In addition Dao et al (2014) [10] shown that the germination and seeding growth of some vegetables were damaged under exposure to microcystins contaminated water from the Dau Tieng reservoir. Agricultural plants showed differently response to cyanobacteria producing microcystins.…”
Section: Introductionmentioning
confidence: 99%